IMPROVING THE STUDENTS’ ABILITY IN CONSTRUCTING IF CONDITIONAL SENTENCES BY APPLYING THE TENSE KEY MATCHING TECHNIQUE AT THE ENGLISH DEPARTMENT OF STKIP INSAN MADANI AIRMOLE - Loly Novita; Muhammad Sabri; Fanalisa Elfa (Politeknik Negeri Bengkalis, 2020)
Abstract: This study was conducted to improve the students’ ability in constructing If conditional sentences by aplying the tense key matching technique. This was a kind of Classroom Action Research. The subject of the study was the second semester students of the English Department of STKIP Insan Madani Airmolek in academic year 2019/2020. The total number of the students were 10. The objectives of the study was to improve the second semester students’ ability in constructing If conditional sentences by applying the Tense Key Matching Technique at English Department of STKIP Insan Madani Airmolek. The study was devided into two cycles in which each cycle has four phases (planning, acting, observing and reflecting. Both quantitative and qualitative data were gathered in this study. Through the result of the study, it shows that there is significant improvement on the students’ ability in constructing If conditional sentences. The mean score of the pre-test in cycle I was 60.7 and the post-test in the same cycle was 74.7. After the technique was applied during the process of teaching and learning, the mean score was higher (84.7).Keywords: Tense key matching technique, If conditional sentences, Students’ ability